Development of Android-Based Learning Media Using Articulate Storyline 3 in Service Company Financial Report Material - Sejati, Adif Akbar; Nurkhin, Ahmad; Santoso, Jarot Tri Bowo; Baswara, Satsya Yoga (Universitas Muhammadiyah Surakarta, 2024)
The research carried out aims to develop Android-based learning media using Articulate Storyline 3 to improve student learning outcomes on service company financial report material. The type of research used is research and development (R&D) using the ADDIE development model (Analyze, Design, Development, Implementation, and Evaluation). The object of this research is students in class X AKL 2 of SMK Negeri 4 Klaten for the 2023–2024 academic year. Data collection was carried out through observation, interviews, tests, and validation questionnaires. Data analysis uses quantitative descriptive to describe the suitability of learning media, while the effectiveness of learning media uses paired sample t tests and N-tests. The results of the data analysis show that the Android-based learning media with articulate storyline 3 obtained a material feasibility score of 75%, a media feasibility score of 57%, a practitioner-teacher feasibility score of 96%, small-scale test student response questionnaires of 88%, and in a large-scale test, students obtained a score of 87%, so theoretically, they were declared suitable for use in learning. The results of the effectiveness of learning media obtained a significance value of 0.00 < 0.05 and an N-test value of 0.47 in the medium category. Based on the results of the data analysis, it can be concluded that Android-based learning media with articulate storyline 3 in service company financial report material is declared suitable for application in accounting learning and effective in improving student learning outcomes.